Developing the global potential of citizen science: Assessing opportunities that benefit people, society and the environment in East Africa. Issue 2 (23rd October 2018) - Pocock, Michael J. O.; Roy, Helen E.; August, Tom; Kuria, Anthony; Barasa, Fred; Bett, John; Githiru, Mwangi; Kairo, James; Kimani, Julius; Kinuthia, Wanja; Kissui, Bernard; Madindou, Ireene; et al.
Abstract: Citizen science is gaining increasing prominence as a tool for science and engagement. However, despite being a potentially valuable tool for sustainable development, citizen science has little visibility in many developing countries. We undertook a collaborative prioritisation process with experts in conservation and the environment to assess the potential of environmental citizen science in East Africa, including its opportunities, benefits and barriers. This provided principles that are applicable across developing countries, particularly for large‐scale citizen science. We found that there was great potential for citizen science to add to our scientific knowledge of natural resources and biodiversity trends. Many of the important benefits of citizen science were for people, as well as the environment directly. Major barriers to citizen science were mostly social and institutional, although projects should also consider access to suitable technology and language barriers. Policy implications . Citizen science can provide data to support decision‐making and reporting against international targets. Participation can also provide societal benefits, informing and empowering people, thus supporting the United Nations' Sustainable Development Goals. In developing countries, innovation is needed to further develop culturally relevant citizen science that benefits participants and end users. This should be supported through regional networks of stakeholders for sharing best practice.